Implementasi Green Human Resource Management Dan Manajemen Risiko Dalam Mendukung Pencapaian Tujuan Pembangunan Berkelanjutan Organisasi Di Balikpapan - Chairullah, Dodi Saputra; Marsianto, Nikolas Heru; Benu, Andika; Andrianto, Farista Cahya (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the effect of Green Human Resource Management and Risk Management on Organizational Sustainable Development Goals Achievement through Green Organizational Culture as a mediating variable in organizations in Balikpapan. This study used a quantitative approach with an explanatory research design. The research sample consisted of 260 respondents from various organizations in Balikpapan and was determined using the number of indicators multiplied by 10 approach. Data were collected through a Likert scale questionnaire ranging from 1 to 5 and analyzed using Structural Equation Modeling-Partial Least Squares with the assistance of SmartPLS. The outer model testing results showed that all constructs met the criteria for convergent validity, reliability, and discriminant validity. The R-square value for Green Organizational Culture was 0.532, indicating that Green HRM and Risk Management were able to explain 53.2% of the variation in Green Organizational Culture. The R-square value for Organizational SDGs Achievement was 0.530, indicating that the model was able to explain 53.0% of the variation in SDGs achievement. The hypothesis testing results showed that Green HRM had a positive and significant effect on Green Organizational Culture with β = 0.367 and p-value = 0.000. Risk Management also had a positive and significant effect on Green Organizational Culture with β = 0.423 and p-value = 0.000. Green Organizational Culture had a positive and significant effect on Organizational SDGs Achievement with β = 0.756 and p-value = 0.000. Green HRM and Risk Management did not have a direct effect on Organizational SDGs Achievement, but both had an indirect effect through Green Organizational Culture.